Epidemiological study of abdominal tuberculosis among Indian migrants and the indigenous population of Leicester, 1972-1989. Issue 8 (August 1992) - Probert, C S; Jayanthi, V; Wicks, A C; Carr-Locke, D L; Garner, P; Mayberry, J F
Abstract : A retrospective, epidemiological study of abdominal tuberculosis in the city of Leicester from 1972 to 1989 is reported. Potential cases were identified from hospital medical records and endoscopy lists, in addition to the county notification register. The city population of 280, 000 included over 75, 000 South Asians. There were 146 cases among South Asians and six in Europeans, four of whom were British. The standardised incidence of abdominal tuberculosis in South Asians decreased significantly from 22.3 cases/10(5)/year during the 1970s to 9.2 cases/10(5)/year in the 1980s (chi 2 = 42, p < 0.001). The incidence during the 1980s was 10.7/10(5)/year in Hindus, 8.7/10(5)/year in Sikhs, and 4.6/10(5)/year in Muslims. The relative risk to Hindus was 2.3 fold greater, and for Sikhs 1.9 fold greater, than that for Muslims, a finding similar to that in pulmonary tuberculosis. The standardised incidence in Europeans was 0.2/10(5)/year and they had significantly less abdominal tuberculosis than South Asians (Z = 8.6, p < 0.001 and relative risk = 46). The standardised mortality ratio was significantly increased in Europeans (standardised mortality ratio = 755, 95% confidence interval 90-2730, chi 2 = 11.4, p < 0.001), but not in South Asians (standardised mortality ratio = 68, 95% confidence interval 20-160). Resection rates were similar between the two ethnic groups. Abdominal tuberculosis still occurs among migrants, and clinicians should remain alert to this in South Asians.